223k views
0 votes
If f(x)

11x + 7, then ,'(x)=1
Enter the correct answer
0000
DONE
Clear all
0
we
in
me
of
is

If f(x) 11x + 7, then ,'(x)=1 Enter the correct answer 0000 DONE Clear all 0 we in-example-1

2 Answers

7 votes
Answer: f^-1(x) = (y - 7)/11

Step-by-step explanation:
f(x) = 11x + 7
y = 11x + 7
y - 7 = 11x
(y - 7)/11 = x

User Krunal Panchal
by
4.4k points
3 votes

Step-by-step explanation:

Hey there!

Given function is f(X) = 11x+7.

Let f(X) be y.

So, y = 11x+7

Interchanging"X" and "y" we get;

X = 11y+7

or, X-7 = 11y

or, y = (x-7)/11

Therefore {f}^{ - 1} (x) = \frac{x - 7}{11} [/tex]

Hope it helps!

User JohannesB
by
5.4k points